Green Banking: The Trend of Maintaining Sustainability of Environmental Business - Fajar Adhitya; Dessy Noor Farida (Global Review of Islamic Economics and Business, 2023)
Various countries are currently facing the degradation of energy resources, natural resources, and environmental pollution. As the party providing financing, banks must participate in reducing environmental damage. Based on interviews conducted with 30 customers who use financing services in banking, the results show that: financing obtained from banks is used for business capital financing, which includes businesses: food stalls, catering, grocery stores, workshops, and expedition services. Based on the interview results, the fact that these businesses have not implemented the concept of an environmentally friendly business is also obtained. This type of research is qualitative research. The data sources for this study were 32 BSI customers in the Central Java region. The findings indicated that 32 respondents of BSI in the Central Java Area are already familiar with green banking. However, when it comes to e-banking, only 37.5% of respondents were aware of green banking. Up to 56.25% of customers realize the need to recycle waste and manage the waste generated by their products. In short, most of BSI's customers in the Central Java region have not implemented the green banking concept in their business. This study's practical implications imply that customers' preferences for using the money they are given to fund environmentally friendly firms may exist. Concerning its theoretical implications, this study aims to improve the theory of green banking and how it relates to the sustainability of businesses. Originality/Value: This research primarily focuses on customer perceptions of the implementation of green banking. However, no research focuses on customer business activities that apply green banking principles, especially MSMEs. At the same time, the customer's business activities are the responsibility of both the business actor and the financier (Bank).